Forest sector sustainability communication in Europe : a systematic literature review on the contents and gaps - Lähtinen, Katja; Toppinen, Anne; Suojanen, Hannele; Stern, Tobias; Ranacher, Lea; Burnard, Michael; Kitek Kuzman, Manja (Springer Nature, 2017)
Purpose of Review - Stakeholder communication plays an important role in enhancing the societal sustainability and business acceptability of the forest sector. The purpose of this study is to present the current state of forest sector communication research with its stakeholders at different hierarchical levels of sustainability (i.e., societal, sectorial, corporate, and product sustainability) in Europe. Recent Findings - A systematic literature review was implemented to acquire information on the research outcomes related to sustainability communication between the forest sector and different stakeholders presented in international peer-reviewed journals between 2005 and 2015. The examined literature emphasizes the role of stakeholder communication for forest sector sustainability and acceptability, but no specific information seems to exist on how to communicate and build the forest sector image in the eyes of different stakeholders. Summary - The gap in the research information indicates that there is a need for more theoretical and empirical work on communication and image-building processes by, e.g., recognizing the specific communication needs of different stakeholders via two-way and proactive information exchange. In the development process of forest sector communication and image building, more efforts on sending well-specified messages for well-targeted audiences should be made.
Keywords: stakeholders; information; channels; acceptability; sustainable development; societal well-being; fi=Markkinointi|en=Marketing|